Methods and instruments of credit risk management inbanks - Харабара, Віолетта; Грешко, Роман Ігорович (Харабара, В., Ткач, І., Грешко, Р., & Харабара, В. (2023). Методи та інструменти управління кредитним ризиком у банках. Журнал політичних наук і досліджень безпеки , 4 (1), 17-24., 2023)
In the article the actuality of the methods of credit risk management system was grounded. The essence of the credit risk was specified, the methods and instruments of management of credit risks were considered as at the level of a separate loan so at the level of created by a bank credit portfolio.
Методи та інструменти управління кредитним ризиком у банках
Keywords: credit risk; banking system; banks; credit activity; risk indicators; financial market